UNVEILING DIASPORIC SHADES OF DRAUPADI’S CHARACTER IN THE PALACE OF ILLUSIONS BY CHITRA BANERJEE DIVAKARUNI - Pareek, Rachana; Sharma, Devendra Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This research paper reconnoiters diasporic dimensions inveterate in the character of Draupadi in Chitra Banerjee Divakaruni’s The Palace of Illusions which is feminist retelling of the Hindu epic The Mahabharata from Draupadi’s perspective. Draupadi’s voice reformed by Divakaruni is amalgamation of diasporic consciousness that is both rooted in tradition as well as entrenched by anxieties of modern existence. Through a feminist and postcolonial lens, the present research paper unveils complex layers of cultural displacement, hybrid identity and psychological exile of Draupadi’s character. Draupadi emerges as a transnational symbol of exile, resistance and identity negotiation rather than existing merely as a mythological figure. Bringing forth Homi Bhabha’s concept of hybridity and Stuart Hall’s fluid identity model this study illustrates how Draupadi transcends time, space and cultural fixity. Her displacement from heaven, internal fragmentation, longing for identity and belonging and assertion of self-narrative are key aspects of diaspora. The Palace of Illusions reconstructs Draupadi’s Narrative as a cultural precinct where diasporic voices reclaim agency, reassemble memory, and rearticulate the feminine within postcolonial mythography.